Differences in the number of some antennal sensilla of four honey bee (Apis mellifera) types and comparisons with the defensive behaviour - Stort, A. C.; Rebustini, M. E. (Int Bee Research Assoc, 1998)
The number of sensilla coeloconica, ampullacea and campaniformia of flagellomeres 3 to 10 of the antennae of workers of four honey bee types (Italian, Caucasian, African and Africanized) was studied by scanning electron microscopy. Comparisons of the four bee types showed that only African and Africanized honey bees did not differ from one another with respect to the number of sensilla coeloconica and ampullacea of flagellomere 10. African and Africanized honey bees and Caucasian and Italian honey bees also did not differ from one another in terms of flagellomere 9. In the other flagellomeres there were no differences among bee types. Italian and Caucasian honey bees differed from Africanized honey bees in terms of number of sensilla campaniformia on flagellomere 6, and Caucasian honey bees differed from African and Africanized honey bees in terms of flagellomere 3. Five significant but random correlation values were obtained between number of antennal sensilla and defensive behaviour in Africanized honey bees. Thus,there is no relationship between antennal structures and defence behaviour.
Keywords: honey bees; Apis mellifera; Apis mellifera caucasica; Apis mellifera ligustica; Apis mellifera scutellata; Africanized honey bees; antennae; antennal sensilla; sensillla coeloconica; ampullacea; defensive behaviour; scanning electron microscopy